2023
DOI: 10.3390/antiox12040928
|View full text |Cite
|
Sign up to set email alerts
|

Role of Advanced Glycation End-Products and Oxidative Stress in Type-2-Diabetes-Induced Bone Fragility and Implications on Fracture Risk Stratification

Abstract: Type 2 diabetes (T2D) and osteoporosis (OP) are major causes of morbidity and mortality that have arelevant health and economic burden. Recent epidemiological evidence suggests that both of these disorders are often associated with each other and that T2D patients have an increased risk of fracture, making bone an additional target of diabetes. As occurs for other diabetic complications, the increased accumulation of advanced glycation end-products (AGEs) and oxidative stress represent the major mechanisms exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 146 publications
0
7
0
Order By: Relevance
“…Different experimental studies have shown that oxidative stress affects osteoblasts, osteoclasts, and osteocytes, causing an imbalance between bone formation and resorption in favor of bone resorption as well as impairing bone mineralization [17][18][19]. Several studies have suggested fenugreek as a potential antioxidant.…”
Section: Discussionmentioning
confidence: 99%
“…Different experimental studies have shown that oxidative stress affects osteoblasts, osteoclasts, and osteocytes, causing an imbalance between bone formation and resorption in favor of bone resorption as well as impairing bone mineralization [17][18][19]. Several studies have suggested fenugreek as a potential antioxidant.…”
Section: Discussionmentioning
confidence: 99%
“…T2D and OP, two prevalent conditions among the elderly, have garnered significant attention due to their intertwined nature (Cavati et al, 2023). While extensive research has shed light on the connection between T2D and OP, the precise molecular mechanisms behind this association remain somewhat elusive, presenting considerable challenges in terms of prevention, diagnosis, and treatment strategies for individuals affected by both ailments (Liu et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies suggest that due to chronic hyperglycemia, the formation of ROS may be associated with collagen glycation, which is an important factor [4,5]. Overall, bone damage in T2DM can be caused by multiple mechanisms: accumulation of advanced glycation end products (AGEs) [79], increased levels of pro-inflammatory cytokines (e.g., IL-6, TNF-α) [80], sclerostin [81], leptin [80], lower levels of OC [11,82]), procollagen I N-terminal propeptide (P1NP) [83,84], parathyroid hormone (PTH) [85], and impairment of osteoblastogenesis [86]. The status of low bone turnover in T2DM is also reflected in lower levels of bone resorption markers (e.g., TRAP5b and C-telopeptide of type I collagen (CTx)) [82,85].…”
Section: Biologically Active Molecules Responsible For Impaired Bone ...mentioning
confidence: 99%